2007
DOI: 10.1038/sj.embor.7401081
|View full text |Cite
|
Sign up to set email alerts
|

AKAP complex regulates Ca 2+ re‐uptake into heart sarcoplasmic reticulum

Abstract: The b-adrenergic receptor/cyclic AMP/protein kinase A (PKA) signalling pathway regulates heart rate and contractility. Here, we identified a supramolecular complex consisting of the sarcoplasmic reticulum Ca 2 þ -ATPase (SERCA2), its negative regulator phospholamban (PLN), the A-kinase anchoring protein AKAP18d and PKA. We show that AKAP18d acts as a scaffold that coordinates PKA phosphorylation of PLN and the adrenergic effect on Ca 2 þ re-uptake. Inhibition of the compartmentalization of this cAMP signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
197
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(213 citation statements)
references
References 19 publications
13
197
0
3
Order By: Relevance
“…Such examples could include metabolic fluxes within the sarcomere 46,47 and "compartmentalized" cyclic adenosine monophosphate (cAMP) signaling via localized Akinase anchor proteins (AKAP) complexes. 48 We, furthermore, see the prospect of using the HSE to describe molecular phenomena well-represented by low-dimensional diffusional processes subject to a potential of mean force, such as the sliding of proteins along DNA. 49,50 …”
Section: Discussionmentioning
confidence: 99%
“…Such examples could include metabolic fluxes within the sarcomere 46,47 and "compartmentalized" cyclic adenosine monophosphate (cAMP) signaling via localized Akinase anchor proteins (AKAP) complexes. 48 We, furthermore, see the prospect of using the HSE to describe molecular phenomena well-represented by low-dimensional diffusional processes subject to a potential of mean force, such as the sliding of proteins along DNA. 49,50 …”
Section: Discussionmentioning
confidence: 99%
“…Hearts were excised, and the ventricles removed. The sinoatrial node, defined as the region bordered by the crista terminalis, the interatrial septum, and the superior and inferior vena cavae (13,15,34,12,22,30), was microdissected at 35°C in a heparinized Tyrode's solution containing (in mM) 140 NaCl, 5.4 KCl, 1.2 KH 2PO4, 5 HEPES, 5.5 D-Glucose, 1 MgCl2, 1.8 CaCl2, and 100 USP/ml heparin, pH adjusted to 7.4 with NaOH. Sinoatrial node tissue was cut into three strips, which were enzymatically digested for 10 -15 min at 35°C with 3.75 mg Liberase TM (Roche, Basel, Switzerland) and 4.75 U elastase (Worthington Biochemical, Lakewood, NJ) in a modified Tyrode's solution containing (in mM) 140 NaCl, 5.4 KCl, 1.2 KH 2PO4, 5 HEPES, 18.5 D-glucose, 0.066 CaCl 2, 50 taurine, and 1 mg/ml BSA, pH adjusted to 6.9 with NaOH.…”
Section: Sinoatrial Myocyte Isolationmentioning
confidence: 99%
“…Displacement of PLB from AKAP18d and siRNA knockdown experiments revealed that scaffolding of the complex by AKAP18d to allow precise spatiotemporal control of PKA phosphorylation of PLB is necessary for adrenergic effect on Ca 2C reuptake (Lygren et al 2007;Fig. 6).…”
Section: Functional Consequences Of Pka Anchoringmentioning
confidence: 99%